ChemInform Abstract: Cycloaddition versus Alkylation Reactions of 2‐Vinylindoles with α, β‐Unsaturated Carbonyl Compounds under Gold Catalysis. Issue 11 (18th March 2014) - Pirovano, Valentina; Dell'Acqua, Monica; Facoetti, Diego; Nava, Donatella; Rizzato, Silvia; Abbiati, Giorgio; Rossi, Elisabetta
Abstract The gold‐catalyzed reaction of N‐ethoxycarbonyl substituted 2‐vinylindoles with α, β‐unsubstituted carbonyl compounds is demonstrated to produce diastereomeric mixtures of Diels—Alder products.